Price Mechanisms in Islamic Economics Perspective of Yahya Bin Umar and Ibn Taymiyah - Lina Pusvisasari; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
This study discusses the role of prices in Islamic economics from the perspective of Yahya bin Umar and Ibn Taymiyah. In the view of Yahya bin Umar, the price mechanism in Islamic economics must follow the principles of justice and transparency and avoid speculation that harms the community. Meanwhile, Ibn Taymiyah argues that the price of goods and services should be determined by market demand and supply, assuming that the market runs freely and there is no fraud. Through a qualitative approach using the literature study method, this article discusses the views of Yahya bin Umar and Ibn Taymiyah on the price mechanism in Islamic economics. The results show that both agree that the price mechanism must follow the principles of fairness and transparency. However, there are differences of opinion in terms of how to determine prices, where Yahya bin Umar emphasizes more on the need for government and community supervision of the price mechanism, while Ibn Taymiyah emphasizes more on market freedom.